Publik Sphere, Sarana Membangun Opini Masyarakat Untuk Mewujudkan Toleransi Dan Harmonisasi Dalam Perspektif Etika Hindu - Hemamalini, Kadek; Suhardi, Untung; Utami Dewi, Dian Syanita (Jayapangus Press, 2025)
The acceleration of technology has another impact on human understanding that is based on holy books. This condition is characterized by the existence of claims of religious truth that only glorify themselves and their groups and look down on religions and groups outside themselves so that religion becomes one of the causes of disharmony in society that often triggers inter-religious conflict. This study raises the issue of how religion has two powers that can unite and divide society and even the country. By using qualitative descriptive analysis based on literature, the researcher conducted an analysis of the meaning of religion, values ​​of tolerance, and harmony from the perspective of Habermas's public sphere concept. Through the application of the principles of religious ethical values, it is hoped that it can contribute to efforts to realize harmony and togetherness in the era of globalization so that open and inclusive communication is established as the key to building shared understanding and reaching a fair agreement. This theory provides an overview of how public space can contribute as an essential framework in a democratic society. The conclusion of this study shows that tolerance is the main indicator for building a strong foundation in society so that it can accept the differences that exist in the public sphere. It is necessary to understand the values ​​of tolerance in Hinduism as a form of spiritual-humanist discussion model to build religious moderation in the era of technological disruption so that public opinion refers to criticism or control carried out by society can influence state policy.